(untitled) (Journal of Economic Research & Business Administration, 2017)
Social security tools are increasingly considered to be a highly effective mechanism for reduction of informal employment since receiving benefits in pension provision is only possible through the legal employment. In this regard the determination of pension provision is necessary for the further development of the pension sphere. Nowadays the various pension systems in the world are based on a combination of three main institutions of pension provision, such as social assistance, compulsory pension insurance and private voluntary insurance. These institutions considered as a tool for poverty reduction in the developed countries and as insurance against risks in order to achieve the minimum required level of life expectancy at retirement age through collective forms of wage earners and “self-employed” people insurance during employment. Institute of funds accumulation on a voluntary basis supports life wealth at retirement and it is one of the main mechanisms of self-protection of workers and small businesses in some countries. The article reveals the basic pension institutions and pension models in different countries.